Management of Corporate Social Responsibility between Profit and Social Responsibility - SINHA, MS. SHRUTI (The journal of contemporary issues in business and government, 2021)
Corporate Social Responsibility (CSR) focuses on many categories of stakeholders and results, including non-organization stakeholders and results that go beyond financial outcomes. Thus, CSR extends the notion of work to go beyond the viewpoint of a mission, job, intra-individual, intra-organizational, and benefit and offers an ideal medium for individuals to try and find meaning through work. We follow a person-centered conceptualization of CSR by concentrating on the making of senses as an underlying and unifying process by which individuals are constructive and conscious agents who search and find meaning by work. Our conceptualization enables us to understand variation in CSR effects due to variation in employee sensitivity and meaningfulness of CSR experience by employees; highlight synergies through disconnected hypotheses and research streams that arise in various disciplines and at the intra-individual, intra-organizational and extra-organizational levels of analysis; and suggest new research. Through using sensory formation as a unifying underlying mechanism, the suggested conceptualization illustrates how individuals find meaningfulness through work and, ultimately, when and why workers perceive CSR in a specific way, which results in more or less positive results for themselves, their organizations and existing stakeholders. Our proposed model may also be used in other research areas that would benefit from (a) putting people in the center stage and their quest for meaningfulness, and (b) concentrating on the role that same-level and cross-level interactions play in the cycle between intra-individual, interpersonal-organizational, and extra-organizational sensing factors.